2016
DOI: 10.3389/fmicb.2016.00931
|View full text |Cite
|
Sign up to set email alerts
|

Siderophore Biosynthesis but Not Reductive Iron Assimilation Is Essential for the Dimorphic Fungus Nomuraea rileyi Conidiation, Dimorphism Transition, Resistance to Oxidative Stress, Pigmented Microsclerotium Formation, and Virulence

Abstract: Iron is an indispensable factor for the dimorphic insect pathogenic Nomuraea rileyi to form persistent microsclerotia which can replace conidia or blastospores for commercial mass production. There are two high affinity iron acquisition pathways in N. rileyi, siderophore-assisted iron mobilization and reductive iron assimilation systems. Transcription of the two iron uptake pathways related genes is induced under iron-limiting conditions. Stage-specific iron uptake-related genes expression during microscleroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 80 publications
1
13
0
Order By: Relevance
“…Indirectly, siderophore production by plant growth promoting microorganisms can avoid the proliferation of plant pathogens through the sequestration of Fe 3+ around the rhizosphere (Gupta et al, 2015;Jha and Saraf, 2015). Some studies indicated that the siderophore production by M. robertsii can play an important role during insect infection and fungal virulence, as well as alleviate the sensitivity of conidia and microsclerotium to oxidative stress and sustain their development under ironlimited conditions (Krasnoff et al, 2014;Donzelli et al, 2015;Li et al, 2016;Sbaraini et al, 2016;Raya-Díaz et al, 2017). Our study was the first to report siderophore synthesis by M. anisopliae (ESALQ 1669) and M. humberi (ESALQ 1638), and our results indicate that siderophore production by some Metarhizium species could be involved in plant growth promotion.…”
Section: Discussionmentioning
confidence: 99%
“…Indirectly, siderophore production by plant growth promoting microorganisms can avoid the proliferation of plant pathogens through the sequestration of Fe 3+ around the rhizosphere (Gupta et al, 2015;Jha and Saraf, 2015). Some studies indicated that the siderophore production by M. robertsii can play an important role during insect infection and fungal virulence, as well as alleviate the sensitivity of conidia and microsclerotium to oxidative stress and sustain their development under ironlimited conditions (Krasnoff et al, 2014;Donzelli et al, 2015;Li et al, 2016;Sbaraini et al, 2016;Raya-Díaz et al, 2017). Our study was the first to report siderophore synthesis by M. anisopliae (ESALQ 1669) and M. humberi (ESALQ 1638), and our results indicate that siderophore production by some Metarhizium species could be involved in plant growth promotion.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, the uptake of nutrients in the human internal environment is an essential for the success of a fungal pathogen ( Abad et al, 2010 ). Currently, no fewer than 37 genes have been associated with the uptake of nutrients in the human internal environment, including through normal nutrient uptake systems and other activated systems ( D’Enfert et al, 1996 ; Brown et al, 2000 ; Hissen et al, 2005 ; Moreno et al, 2007 ; Schrettl et al, 2007 ; Al-Bader et al, 2010 ; Amich et al, 2010 ; Li et al, 2016 ). Thirty-six of these 37 homologous genes have been found in P. capsulatum .…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, the signalling network that regulates the chitin synthesis‐ and pigment synthesis‐associated genes in solid SMAY and liquid AM culture is highly complicated. Major basal salts such as iron and calcium cations are necessary for MS formation (Song et al ., 2014) and SidA is the major pathway of cellular iron uptake for MS formation (Li et al ., 2016). We demonstrated that the iron importer and calcium transports, Ct‐1 and Ct‐2, were important in MS formation (Wang and Yin, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…The switching rates of the tested strains were counted as previously described (Li et al ., 2016). Approximately 100 simple yeast cells were pipetted onto SMAY medium and grown at 25°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation